The Praxeological Level of Supporting the Continuity of Education During the Child’s Transition to School - Teleková, Radka (Journal of Education Culture and Society, 2025)
Aim. The presented paper is aimed at finding out and comparing the opinions of teachers of pre-primary education and primary education on selected activities to support the continuity of education during the child’s transition to school. With this aim, pedagogical research was carried out with teachers in Slovakia. Methods. The method used was a questionnaire in which scale questions were used. We statistically evaluated the research findings using descriptive statistics methods. Results. The conduct of the research and the analysis of the results confirmed that there are statistically significant differences in the teachers’ opinions on the selected activities to support the continuity of education towards both teachers and parents. We found statistically significant differences to the following answers: “use of elements from kindergarten in work with beginning schoolchildren/ from elementary school in the preparation of future schoolchildren” and “informal contacts, alternative methods of communication between teachers”. The results show the same teachers´perception of the activities: “use of elements from kindergarten in work with beginning schoolchildren/ from elementary school in the preparation of future schoolchildren” and “informal contacts, alternative methods of communication between teachers” The continuity of knowledge, experience and skills creates a basis for optimal child´s transition from kindergarten to primary school. Conclusion. Our research activity investigated the attitudes of kindergarten and primary school teachers towards various support mechanisms designed to ensure a smooth transition for children entering primary education. The findings revealed a divergence of opinion on this topic between the two groups - kindergarten teachers and primary school teachers.